2020
DOI: 10.1261/rna.073692.119
|View full text |Cite
|
Sign up to set email alerts
|

Ppp1r1b-lncRNA inhibits PRC2 at myogenic regulatory genes to promote cardiac and skeletal muscle development in mouse and human

Abstract: Long noncoding RNAs (lncRNAs) have emerged as critical epigenetic regulators and play important roles in cardiac development and congenital heart disease. In a previous study, we identified a novel lncRNA, Ppp1r1b, with expression highly correlated with myogenesis. However, the molecular mechanism that underlies Ppp1r1b-lncRNA function in myogenic regulation is unknown. By silencing Ppp1r1b-lncRNA, mouse C2C12 and human skeletal myoblasts failed to develop fully differentiated myotubes. Myogenic differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…At the post-transcriptional level, lncRNA can serve as efficient microRNA (miRNA) sponges—termed competing endogenous RNAs (ceRNAs)—that interact with miRNA to regulate gene expression. 6 Recently, numerous lncRNAs have been identified in humans and other organisms that play diverse roles in regulating various phenomenon, such as cell proliferation and apoptosis, 7 , 8 cell development, 9 cell differentiation, 10 and development of certain diseases. 11 , 12 Specifically, lncRNAs are involved in regulating spermatogenesis, 13 , 14 steroidogenesis, 15 embryo implantation 16 and development, 17 follicular development, 18 oocyte maturation, 19 GC apoptosis and proliferation, 20 , 21 and reproductive diseases, 22 , 23 suggesting their importance in reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…At the post-transcriptional level, lncRNA can serve as efficient microRNA (miRNA) sponges—termed competing endogenous RNAs (ceRNAs)—that interact with miRNA to regulate gene expression. 6 Recently, numerous lncRNAs have been identified in humans and other organisms that play diverse roles in regulating various phenomenon, such as cell proliferation and apoptosis, 7 , 8 cell development, 9 cell differentiation, 10 and development of certain diseases. 11 , 12 Specifically, lncRNAs are involved in regulating spermatogenesis, 13 , 14 steroidogenesis, 15 embryo implantation 16 and development, 17 follicular development, 18 oocyte maturation, 19 GC apoptosis and proliferation, 20 , 21 and reproductive diseases, 22 , 23 suggesting their importance in reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Myogenic and specification and differentiation of the heart are complex biological processes determined by the activities of gene regulatory networks. At the molecular level, emerging studies have confirmed the role of long noncoding RNAs (lncRNAs) in controlling major biological processes that affect stem cell differentiation and development [ 10 , 11 ]. For instance, it was shown that lncRNA Fendrr and Braveheart ( Bvht ) is essential for proper fate control of lateral mesoderm derivatives [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for cardiac development, Braveheart (BVHT) lncRNA was the first lncRNA found to be necessary for the activation of important cardiac genes and transcription factors for cardiogenic differentiation and development [ 161 , 162 ]. Following that, many studies have identified other lncRNAs such as Fendrr [ 163 ], Linc1405 [ 164 ], HoxBlinc RNA [ 165 ], Handsdown ( Hdn ) [ 166 ] in mice, and (CAR)diac (M)esoderm (E)nhancer-associated (N)on-coding RNA ( CARMEN ) [ 167 ], Heart Brake LncRNA 1 ( HBL1 ) [ 168 ] and Ppp1r1b [ 169 ] in human. The majority of these lncRNAs interact with Polycomb repressive complex-2 (PRC2), a histone methyltransferase responsible for epigenetic silencing during the development of the heart and body wall [ 170 ].…”
Section: Long Non-coding Rnas In Cvdmentioning
confidence: 99%